Functional and microstructural neurosubstrates between apathy and depressive symptoms in dementia - Sheng-Min Huang; Yen-Hsuan Hsu; Jir-Jei Yang; Chien-Yuan Lin; Min-Chien Tu; Li-Wei Kuo (NeuroImage: Clinical)
The overlapping features of depressive symptoms and apathy hinder their differentiation in clinical practice, and hence a greater understanding of their neurosubstrates in dementia and its subtypes is necessary. Ninety-two dementia patients (Alzheimer’s disease [AD, n = 52]; subcortical ischemic vascular disease [SIVD, n = 40]), and 30 cognitively normal subjects were evaluated using the Apathy Evaluation Scale (AES), Beck’s Depression Inventory (BDI), and brain magnetic resonance imaging (MRI). Grouped by AES/BDI scores, and hubs of depression/apathy were identified by comparing MRI metrics including fractional amplitude of low-frequency fluctuation (fALFF) of resting-state functional MRI, and mean kurtosis (MK) of diffusion kurtosis imaging. Associations between the hubs with depressive and apathy symptoms were analyzed. Comparing low-AES and high-AES groups, fALFF indicated pervasive changes mainly within the default mode network (DMN) and frontoparietal network (FPN). Comparing low-BDI and high-BDI groups, fALFF reflected changes within the DMN, FPN, and salience network (SAN). Contrarily, MK showed focal changes within DMN and SAN regions from the same group-wise comparisons. While fALFF was more correlated with DMN/FPN for AES than BDI and more significantly correlated with SIVD than AD, MK was more correlated with the left anterior cingulate cortex and right insula for AES than BDI, but more significantly correlated with AD than SIVD (all P < 0.01). Topologically, the fALFF hubs for AES and BDI centered at the posterior and anterior poles, respectively. These findings suggest that dual-modal MRI could reflect the distinct neuropathological basis for apathy and depressive symptoms in AD and SIVD.